â€œANALISIS DAN INTERPRETASI DATA WELL LOGGING BERDASARKAN PARAMETER PETROFISIKA PADA SUMUR SOUTH ONIN AI-X DAN SUMUR NORTH ONIN-1X DI LAPANGAN X PAPUAâ€ - Intan, INTAN APRILIA NINGSIH; Isnawan , Dianto (ReTII, 2022)
Well Logging is a method that can provide the data needed to evaluate qualitatively and quantitatively the presence of a hydrocarbon zone. This study aims to determine the reservoir zone based on petrophysical parameters. The object of the research is the South Onin AI-X Well and the North Onin-1X Well which are located in the Basin in eastern Indonesia, which have the potential for hydrocarbons. The South Onin 1A-X well is based on the degree of separation between density logs and neutrons. The type of hydrocarbon fluid content consists of water and oil spread over the reservoir zone and at different depths. In the North Onin-1X well, based on the level of separation between density logs and neutrons, it is indicated that the type of hydrocarbon fluid content consists of water and oil spread over the reservoir zone and at different depths. In both wells, no indication of gaseous hydrocarbon fluid was found.